PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMAN 1 SUNGAI RUMBAI - Octaviani, Sheila (Jurnal Edukasi dan Penelitian Matematika, 2023)
One indicator of the success of students in mastering mathematics is seen from the results of learning mathematics. However, in reality mathematics learning outcomes of grade XI  students of SMA Negeri 1 Sungai Rumbai, shows that the students' mathematics learning outcomes remains relatively low. The solution that can be applied by educators to improve students' math learning outcomes is the Student Teams Achievement Division type cooperative learning model. This study aims to determine, describe and analyze whether the mathematics learning outcomes of students who learn with the cooperative learning model type Student Teams Achievement Division are better than students who learn with conventional learning models in classl XI SMA Negeri 1 Sungai Rumbai. Quasi experiment with Posttest Only Design with Non-equivalent Group is used in this research. Based on the results of data analysis and hypothesis testing, it shows that the mathematics learning outcomes of students who learn with the Student Teams Achievement Division type  cooperative learning model are better   than students who learn with conventional learning models in class XI IPA SMA Negeri 1 Sungai Rumbai.Keywords– Cooperative, Student Teams Achievement Division, Mathematics Learning Outcomes.